Manual Compression versus Suture-Mediated Closure Device Technique for VA-ECMO Decannulation - Clemens Scherer; Christopher Stremmel; Enzo Lüsebrink; Thomas J. Stocker; Konstantin Stark; Carmen Schönegger; Antonia Kellnar; Jan Kleeberger; Maja Hanuna; Tobias Petzold; Sven Peterss; Daniel Braun; et al. (Journal of Interventional Cardiology)
Background. The impact of devices for vessel closure on the safety and efficacy of cannula removal in VA-ECMO patients is unknown. Methods. We retrospectively analyzed 180 consecutive patients weaned from VA-ECMO after cardiac arrest or cardiogenic shock from January 2012 to June 2020. In the first period (historical technique group), from January 2012 to December 2018, primary decannulation strategy was manual compression. In the second period (current technique group), from January 2019 to June 2020, decannulation was performed either by a conventional approach with manual compression or by a suture-mediated closure device technique. Results. A femoral compression system was necessary in 71% of patients in the historical group compared to 39% in the current technique group (p < 0.01). Vascular surgery was performed in 12% in the historical cohort and 2% in the current technique cohort, which indicated a clear trend, albeit it did not reach significance (p = 0.07). Conclusion. We illustrated that a suture-mediated closure device technique for VA-ECMO decannulation was feasible, safe, and may have reduced the need of surgical interventions compared to manual compression alone.